Laser-induced photoconductivity of ferromagnetic semiconductors - Semchuk, O.Yu.; Bila, R.V.; Willander, M.; Karlsteen, M. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
The influence of a strong electromagnetic wave on the kinetic phenomena in ferromagnetic semiconductors (FMSC) is considered. To sequentialy consider this influence, we obtained quantum kinetic equations for electrons and magnons involved into the process of electron-magnon interaction at presence of intense high-frequency electromagnetic field. The new mechanism of a photoconduction not bound with a change of the number of carriers in the conduction band of FMSC and hot conduction electrons is offered. The density of electric current in the FMSC provided by strong variable electromagnetic field and feeble constant electric field has been calculated. The valuation of FMSC electric conductivity in the infrared spectral range is made. It is shown that magnification of the amplitude of variable electromagnetic filed results in increasing the conductivity of FMSC at some fixed temperature.